2022
DOI: 10.1002/micr.30926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the long‐term results of vascular anastomosis using polyurethane adhesive and shape‐memory stent in the rat carotid artery model

Abstract: Introduction:In free flaps, 5%-10% of complications are related to failure of sutured vascular anastomoses. Adhesive-based microvascular anastomoses are potential alternatives but are associated with failure rates of 70% in research studies. VIVO is a new adhesive with slow biodegradation within 6 months that has shown a 100% patency rate in research studies over 2 h observation time but long-term patency has not been evaluated. The authors hypothesize that VIVO will enable a reliable microvascular procedure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Nevertheless, a major disadvantage of collagen sponges is that they are made of animal native type I and type III collagens [46], and these, like any xenogeneic preparation, pose an increased risk of allergic, immunologic, and even anaphylactic reactions [47]. In rat studies, VIVO showed sufficient hemostasis under moist conditions when applied in a sealing fashion to vascular anastomoses [20,24]. In the histologic evaluation, VIVO showed comparable thrombus formations when compared to extraction sockets treated with GSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a major disadvantage of collagen sponges is that they are made of animal native type I and type III collagens [46], and these, like any xenogeneic preparation, pose an increased risk of allergic, immunologic, and even anaphylactic reactions [47]. In rat studies, VIVO showed sufficient hemostasis under moist conditions when applied in a sealing fashion to vascular anastomoses [20,24]. In the histologic evaluation, VIVO showed comparable thrombus formations when compared to extraction sockets treated with GSP.…”
Section: Discussionmentioning
confidence: 99%
“…The novel polyurethane-based tissue adhesive VIVO (Adhesys Medical GmbH, Aachen, Germany) is an innovative biodegradable adhesive that has demonstrated rapid and safe application [20]. It is an alternative to conventional hemostasis [21][22][23] with favorable tissue compatibility [24], as evidenced by good biocompatibility during the various degradation phases [23].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) hydrogels, represented by FocalSeal and TissuGlu, boast adaptability and biocompatibility, making them valuable for the dynamic realm of vascular anastomosis [ 104 , 105 ]. Polyurethane-based adhesives add another dimension of choice in the anastomosis toolkit [ [106] , [107] , [108] ]. Furthermore, polysaccharide-based adhesives, derived from natural sugars, guarantee both biodegradability and biocompatibility, ensuring effective vascular seals with minimized inflammation [ [109] , [110] , [111] ].…”
Section: Sutureless Anastomotic Approaches Undergoing Developmentmentioning
confidence: 99%
“…A novel biodegradable polyurethane-based adhesive, VIVO, was introduced as an additional safety measure in surgical procedures [ [106] , [107] , [108] ]. Comprising an isocyanate-functionalized prepolymer and an amino-based curing agent, VIVO exhibited impressive adhesive strength on wet tissues.…”
Section: Sutureless Anastomotic Approaches Undergoing Developmentmentioning
confidence: 99%
See 1 more Smart Citation